Imaging and Circulating Biomarker-Defined Cardiac Pathology in Pulmonary Tuberculosis: A Systematic Review - Marcello S. Scopazzini; Katherine J. Hill; Edith D. Majonga; Dominik Zenner; Helen Ayles; Anoop S. V. Shah (Global Heart)
Background: Pulmonary tuberculosis (PTB) is associated with increased cardiovascular disease (CVD) mortality. However, underlying pathophysiological mechanisms are poorly understood. This systematic review aims to synthesize the evidence on the prevalence of cardiac pathology based on cardiac imaging and circulating biomarkers in patients with PTB. Methods: We systematically searched databases for studies in patients with PTB evaluating cardiac pathology (pericardial effusion or left ventricular dysfunction) on echocardiography; late gadolinium enhancement on cardiac magnetic resonance imaging (CMR); myocardial inflammation on positron-emission tomography (PET); coronary artery stenosis on CT coronary angiography (CTCA); and cardiac troponin (cTn) and/or B-type natriuretic peptides (BNP) assessment. Results: Seven studies were included across 1,333 participants with PTB. Four studies used echocardiography (n= 1,111). The prevalence of pericardial effusion ranged from 14.1- 55.9%; and left ventricular systolic impairment from 0 - 4.25%. One study used CMR and PET-CT (n=26); and two studies used PET-CT alone (n=196). The prevalence of pericardial and/or myocardial inflammation ranged from 0.6 - 21.8%. One study evaluated cTn, Creatine Kinase-MB (CK-MB), and BNP (n=800), of whom 246 had raised cTn. No study reported cardiac pathology using CTCA. Conclusion: Pericardial effusion is the commonest reported cardiac pathology in PTB. To date, only one study has evaluated cardiac biomarkers and studies evaluating myocardial or coronary disease on advanced imaging remain limited. Our study highlights the paucity of evidence on the presence of cardiac pathology in PTB. Studies are required to determine the prevalence of, and disease mechanisms associated with cardiac pathology among patients with PTB.